Mechanics of back-plate reinforced structure for server CPU assembly under mechanical loading: Measurements and simulation - Liao, M. C.; Huang, P. S.; Huang, T. C.; Tsai, M. Y. (Proceedings of technical papers (International Microsystems, Packaging, Assembly, and Circuits Technology Conference. Print), 2014)
The objective of the study is to investigate the mechanical behavior of the back-plate reinforced central processing unit (CPU) assembly structure during component assembling, or under mechanical loadings such as the screw tightening torque and an independent loading mechanism (ILM) clamping forces experimentally and numerically. In the experiments, the strain gauge technique and shadow moiré measurement are applied for determining the loading-induced strains and out-of-plane deformations of the structure, respectively, on a printed circuit board (PCB) and a back plate. In the numerical simulation, the finite element method (FEM) is used for simulating the deformation and strains of the structure to understand the mechanics. Experimental results show that the screw torque force has no effect on the deformation of the PCB and the back plate, but the reinforcement of the PCB by the back plate to avoid bending deformation is pronounced. In addition, the assembly of the heat sink would induce 38% more bending strain on the PCB, compared with only the CPU assembly. The simulation results indicate that the PCB and the back plate subject to ILM clamping forces would deform in cylindrical bending mainly in the longitudinal direction. The bending deformations of the back plate and PCB have been successfully validated through its good consistency with moiré experiment as well as strain gauge data.